Pelatihan dan Pendampingan Penulisan Karya Ilmiah Remaja bagi Siswa/i SMA/Sederajat di Kecamatan Muara Jawa, Kabupaten Kutai Kartanegara - Casmudi Casmudi; Ryan Angga Pratama (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2019)
Many schools only provide intensive mentoring or guidance if there is an agenda to take part in the competition to write scientific papers. But not a few who did not hold these activities, so students did not participate in the competition writing scientific papers. During this time the assistance in facing scientific writing competition was only focused on the problem of writing patterns and content of students' scientific writing. The accompanying teacher mostly corrects the writing and then agrees to be included in the competition. In addition, students' interest in participating in these competitions is also very minimal. For this reason, the need for the provision of Training and Mentoring for Youth Scientific Writing for Students of the High School / Equivalent in Muara Jawa District, Kutai Kartanegara Regency. The results obtained were from 9 groups of students formed during the activity, only 1 group was still conducting consultation and assistance online via email. This shows that students' interest is still lacking and this is a service evaluation so that in the future they can provide more time in activities like this. Keywords: youth scientific writing, training